1985
DOI: 10.1002/joc.3370050507
|View full text |Cite
|
Sign up to set email alerts
|

The separate contributions of line squalls, thunderstorms and the monsoon to the total rainfall in nigeria

Abstract: Using thunderstorm and rainfall information from five Nigerian stations for a five year period, the separate contributions of line squalls, thunderstorms and ordinary monsoons to the total rainfall and their variations with latitude are investigated. Total and thunderstorm rainfall decreases with increasing latitude but monsoon precipitation decreases exponentially while line squall rainfall is at a maximum around 9"N. Rainfall from thunderstorms shows a single annual peak in July/August at stations north of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 9 publications
(5 reference statements)
4
53
1
Order By: Relevance
“…The disparity may be due partly to the fact that their rain events did not discriminate between precipitating and non-precipitating storms. Also, Omotosho (1985) showed that in August, there is some contribution to rainfall from the 'monsoon rain' (meso-scale convective systems with only an occasional thunder over a period consisting of 945 several hours) over areas north of 11°N. The difference between the raindays and storms may also be due to this effect.…”
Section: Storm Occurrences and Their Precipitation Deliverymentioning
confidence: 99%
See 3 more Smart Citations
“…The disparity may be due partly to the fact that their rain events did not discriminate between precipitating and non-precipitating storms. Also, Omotosho (1985) showed that in August, there is some contribution to rainfall from the 'monsoon rain' (meso-scale convective systems with only an occasional thunder over a period consisting of 945 several hours) over areas north of 11°N. The difference between the raindays and storms may also be due to this effect.…”
Section: Storm Occurrences and Their Precipitation Deliverymentioning
confidence: 99%
“…The long-term data for evaluating the anomalies were obtained from Aspliden and Adefolalu (1976), which was based on actual radiosonde observations over West Africa. Omotosho (1985Omotosho ( , 1987 distinguished between two groups of storms in Nigeria -in situ and slow-moving storms (maximum gusts <12 ms −1 ) and squall lines with gusts greater than 12 ms −1 . The first group occurs mostly between 1200 and 2400 h while squall lines affect Kano after 2400 h (Omotosho, 1987).…”
Section: Data and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Unsurprisingly, Ochei et al [7] also showed that the occurrence of thunderstorms tends to be greatly reduced over Maiduguri (North-eastern Nigeria) than over Sokoto (North-western Nigeria). However, further studies [8][9][10][11] have revealed the occurrence of upper-level downdrafts at the sides of the upper portion of updrafts.Most works on mesoscale convective systems ranges from its contribution to total precipitation [2,6,12], frequency of occurrences of such systems [7] to the damages it has caused over-time [13][14][15], but none has been written explicitly on the implication of the changing climate on the frequency of occurrence of these mesoscale convective systems. This is an area where changing climate variables, have the tendency of affecting either negatively (positively), by decreasing (increasing) the number of occurrence of thunderstorm in a given time frame.…”
mentioning
confidence: 99%